An examination of the internal auditors' whistleblowing likelihood upon awareness of occupational fraud occurrence - Muhammad Hariz, Hamid (2017)
This study examines the internal auditors' whistleblowing likelihood upon awareness of occupational fraud occurrence. For that purpose, Graham's model of principled organizational dissent was employed due to its relevance to accounting context. Apart from the existing perspectives of the model, influences of the three dimensions relevant to the model were also assessed. Additionally, the interaction effects between these dimensions and some demographic factors were also analyzed. Furthermore, in light of organizational support theory, the current study also gauged the likelihood to blow the whistle among internal auditors from the perspective of perceived organizational suppo1t. To attain the objectives, as well as to answer the research questions, some internal auditors who work for the Malaysian public listed companies in several sectors were selected randomly through a two-stage sampling. In testing the current study's hypotheses, regression analyses, as well as analysis of variance (ANOVA) procedure were used. Out of the three perspectives of the principled organizational dissent model, only the perceived seriousness of wrongdoing has significantly predicted the dependent variable. Even though all the three manipulated variables are related to the whistleblowing likelihood, however, none of the demographic factors has a significant moderating role in influencing the dependent variable. The result of the present study reveals that the perceived organizational support is not only related, but has also significantly and positively predicted the internal auditors' whistleblowing likelihood. Apart from providing empirical evidence to the existing literature, this study offers significant insights into the theory and practice. Generally, this study affirms that the theoretical integration can better understand whistleblowing likelihood among internal auditors. Besides offering some 'whistleblower-friendly' policies and procedures. it is also suggested for organizations to maintain effective control system to mitigate occupational fraud occurrence, as well as to provide better quality evidence for the internal auditors' reporting purposes.